2021
DOI: 10.1101/2021.01.11.426275
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Screening by deep sequencing reveals mediators of microRNA tailing inC. elegans

Abstract: AbstractmicroRNAs are frequently modified by addition of untemplated nucleotides to the 3’ end, but the role of this tailing is often unclear. Here we characterize the prevalence and functional consequences of microRNA tailing in vivo, using the C. elegans model. MicroRNA tailing in C. elegans consists mostly of mono-uridylation of mature microRNA species, with rarer mono-adenylation which is likely added to microRNA precursors. Through a targeted RNAi screen, we discover that the TUT4/TUT7 gene family member … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 90 publications
(192 reference statements)
4
11
0
Order By: Relevance
“…In embryos and L1s, we observed that miRNAs are tailed to various extents, though generally not very high levels (Figure 3A, Figure S6A). Tailing was mostly mono-uridylation, with some miRNAs displaying significant adenylation or cytidylation, as previously observed (Figure 3A, Figure S6A) (Vieux et al, 2021). Overall tailing and miRNA abundance were not correlated, and the mir-35 family members were generally high in abundance, with a wide range of tailing frequencies observed across different members (Figure 3B, Table S4).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…In embryos and L1s, we observed that miRNAs are tailed to various extents, though generally not very high levels (Figure 3A, Figure S6A). Tailing was mostly mono-uridylation, with some miRNAs displaying significant adenylation or cytidylation, as previously observed (Figure 3A, Figure S6A) (Vieux et al, 2021). Overall tailing and miRNA abundance were not correlated, and the mir-35 family members were generally high in abundance, with a wide range of tailing frequencies observed across different members (Figure 3B, Table S4).…”
Section: Resultssupporting
confidence: 84%
“…We and others previously observed slight increases in the prevalence of tailed and trimmed miRNAs as miRNAs approach decay (Baccarini et al, 2011; Kingston and Bartel, 2019; Vieux et al, 2021). In TDMD, miRNAs often experience very high levels of tailing and/or trimming (generally ≥20-40% tailed or trimmed isoforms) (Ameres et al, 2010; Baccarini et al, 2011; Bitetti et al, 2018; Cazalla et al, 2010; Ghini et al, 2018; Kleaveland et al, 2018; Li et al, 2021; Marcinowski et al, 2012).…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…By contrast, whether or not miRNA tailing determines miRNA stability remains debatable. Consistent with several recent studies 35,53,54 , we found that the loss of uridylation or adenylation did not coincide with changes in miRNA abundance at a global scale. This suggests that 3’ tailing does not play a general role in miRNA turnover.…”
Section: Discussionsupporting
confidence: 91%
“…These structural data raise the question of potential uncoupling between TDMD and tailing and trimming since the miRNA become available for modification in this conformation (discussed in Pawlica et al, 2019). Accordingly, other studies demonstrate that the tailing and trimming machineries are implicated in miRNA decay but not strictly required for TDMD (Yang et al, 2020) and that the disruption of tailing has no impact on miRNA turnover (Vieux et al, 2021).…”
Section: Risc Binding Outcomesmentioning
confidence: 99%